EVALUATION OF SOME FORMULATED DIETS FOR RE ING T POST-LARVAE OF MACROBRACHIUM ROSENBERGH - Indulkar, S. T.; Belsare, S. G. (Journal of Indian Fisheries Association, 2015)
Macrobrachium rosenbergii post-larvae with an average weight of 6.26 t 0.23 mg and an average length of 10.67 t 0.13 mm were fed with one of the five experimental diets having graded levels of lipid (5.0, 7.5, 10.0, 12.5 and 15.0%) to satiation two times a day to study their effect on growth, survival and feed utilisation. The highest weight gain was observed in post-larvae fed 7.5% lipid, although there was no significant difference (p > 0.05) between groups fed 7.5 and 10.0% lipid. Similar effect was observed in the specific growth rate and protein efficiency ratio of post-larvae fed the diet with 7.5 and 10.0% lipid. The lowest feed conversion ratio was obtained in postlarvae fed the diet with 7.5% lipid. The survival rates of post-larvae fed on various levels of dietary lipid differed significantly (p < 0.05) after 15 days of rearing period. Significantly lower survival was observed in the diet with 15.0% lipid level. Dietary lipid did not significantly affect prawn carcass protein, lipid and ash contents. Based on the data analysis (ANOVA - one way analysis), the dietary lipid requirement for 15 days of nursery rearing of Macrobrachium rosenbergii post-larvae was estimated to be 7.5 to 10.0% under experimental conditions in this study. Keywords: Macrobrachium rosenbergii, post-larvae, nursery rearing, formulated diets, lipid requirement